Prognostic factors and their role in the histological classification of cutaneous squamous cell carcinoma (Research, Society and Development, 2021)
Squamous cell carcinoma (SCCs) is a malignant epithelial tumor of keratinocytes, composed of heterogeneous cells with varied phenotypes, which occurs mainly in glabrous regions, with little or no pigmentation. It is a common neoplasm in dogs, cats, horses and cattle, relatively uncommon in sheep and rare in goats and pigs. This study aimed to carry out a critical review of the different histopathological classification systems for cutaneous SCCs and their impact on the definition of the prognosis. Human medicine has several classification systems for oral and cutaneous SCCs, such as the Broders system (1925) that proposes a gradation based on cell differentiation, and Bryne (1992), which is based on the multifactorial graduation of malignancy, evaluating four morphological characteristics, for which scores are assigned and which after the sum of the scores, result in a degree. In veterinary medicine, the most used classification system is that of Weiss and Frese (1974), based on the degree of differentiation. However, Nagamine et al. (2017) developed a multifactorial classification system for malignancy grading for oral and cutaneous SCCs in dogs, evaluating five morphological characteristics for which scores are assigned (from 1 to 4) and added together, result in a grade. Each of the systems is based and one or more factors considered as prognostications. These classification systems can have advantages and disadvantages, being necessary to know in depth the different aspects of each one so that one can choose the one that contemplates the diagnostic purpose.